The Influence of Internal and Macroeconomic Factors on Bank Profitability Moderated by Asset Quality - Rully Hardiansyah; Samuel Yosafat Beso; Susy Muchtar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the impact of internal bank factors, including solvency (CAR), liquidity (LDR), and credit risk (NPL), as well as macroeconomic factors such as Gross Domestic Product (GDP) and inflation, on bank profitability measured by Return on Assets (ROA). In addition, the study examines the moderating role of Asset Quality (AQ) in influencing the relationship between independent variables and ROA. The data used in this research are derived from the financial statements of conventional banks in Indonesia and macroeconomic indicators covering the 2019–2024 period. The analysis is conducted using panel data regression with a moderation approach, applying the Generalized Least Squares (GLS) method and robustness testing with the Generalized Method of Moments (GMM). The results indicate that internal and macroeconomic variables collectively exert a significant influence on bank profitability. Partially, credit risk (NPL), asset quality (AQ), and bank size (SIZE) show statistically significant effects on ROA. Higher credit risk reduces profitability, while larger banks achieve greater efficiency and returns due to economies of scale. Asset quality demonstrates a dual role enhancing or constraining profitability depending on its management effectiveness. Moreover, AQ significantly moderates the relationship between internal and external factors, emphasizing the importance of prudent credit management and sound asset allocation for sustainable profitability in Indonesia’s banking sector.